Symplectic chain complex and reidemeister torsion of compact manifolds - Sözen, Yaşar (MATHEMATICA SCANDINAVICA, 2012)
Using symplectic complex, this article proves a formula for computing the Reidemeister torsion of even dimensional oriented closed connected manifolds. Moreover, it presents applications to Riemann surfaces and Grassmannians.